Transplantation of Predegenerated Peripheral Nerves after Complete Spinal Cord Transection in Rats: Effect of Neural Precursor Cells and Pharmacological Treatment with the Sulfoglycolipid Tol-51 - Alejandro Arriero-Cabañero; Elisa García-Vences; Stephanie Sánchez-Torres; Sergio Aristizabal-Hernandez; Concepción García-Rama; Enrique Pérez-Rizo; Alfonso Fernández-Mayoralas; Israel Grijalva; Vinnitsa Buzoianu-Anguiano; Ernesto Doncel-Pérez; Jörg Mey (Cells, 2024)
Following spinal cord injury (SCI), the regenerative capacity of the central nervous system (CNS) is severely limited by the failure of axonal regeneration. The regeneration of CNS axons has been shown to occur by grafting predegenerated peripheral nerves (PPNs) and to be promoted by the transplantation of neural precursor cells (NPCs). The introduction of a combinatorial treatment of PPNs and NPCs after SCI has to address the additional problem of glial scar formation, which prevents regenerating axons from leaving the implant and making functional connections. Previously, we discovered that the synthetic sulfoglycolipid Tol-51 inhibits astrogliosis. The objective was to evaluate axonal regeneration and locomotor function improvement after SCI in rats treated with a combination of PPN, NPC, and Tol-51. One month after SCI, the scar tissue was removed and replaced with segments of PPN or PPN+Tol-51; PPN+NPC+Tol-51. The transplantation of a PPN segment favors regenerative axonal growth; in combination with Tol-51 and NPC, 30% of the labeled descending corticospinal axons were able to grow through the PPN and penetrate the caudal spinal cord. The animals treated with PPN showed significantly better motor function. Our data demonstrate that PPN implants plus NPC and Tol-51 allow successful axonal regeneration in the CNS.